Adoption of seismic-resistant techniques in reconstructed housing in the aftermath of Nepal's 2015 Gorkha earthquake. Issue 4 (November 2021) - Hendriks, Eefje; Opdyke, Aaron
Earthquake affected households too often insufficiently apply seismic construction knowledge during reconstruction. This study aims to assess to what degree safety guidelines have found their way to practice in Nepal. Differences are explored between communities in the Gorkha and Okhaldhunga districts, which received differing levels of technical assistance following the 2015 earthquakes. Seismic resistance of houses was assessed 3 years after the earthquakes. Findings from 955 houses in 25 communities show high degrees of adoption of earthquake-resistant construction knowledge in all selected communities. Variation in safer construction across communities differs only slightly for different intensities of humanitarian technical assistance. This finding points toward the need to more closely examine the communication methods employed and motivations of households to build back safer.